A comparative study on anti-smoking law and policy in Malaysia and Australia / Ahmad Naqiuddin Ramli …[et al.] - Ramli, Ahmad Naqiuddin; Zainordin, Amirul Azim; Mat Hussain, Azwan; Ahmad, Mohd Hafizi (2010)
The title of our project is A Comparative Study on Anti-Smoking Law and Policy in Malaysia and Australia. This research paper will explain about adequacy of the law and policies against smokers with reference to the law and policies that govern both countries. In this study, comparison between the two states in regards to implementation of law, the legal and non-legal effect on the issue of smoking will be considered. The purpose of this project paper is to analyze whether there is sufficient enforcement in implementation of the law and policy on the issue of smoking. The other purpose is to analyze whether the campaign and fatwa which banned smoking in Malaysia is sufficient and effective in order to curb the problem of smoking. For this paper project, we have conducted qualitative type of research that consists of library - based and Internet research. This procedure is very helpful and useful as it provides vast and fast resources which are significant to the research.